Nanodrug delivery in reversing multidrug resistance in cancer cells - Kapse-Mistry, Sonali; Govender, Thirumala; Srivastava, Rohit; Yergeri, Mayur (Frontiers in Pharmacology, 2014)
Different mechanisms in cancer cells become resistant to one or more chemotherapeutics is known as multidrug resistance(MDR) which hinders chemotherapy efficacy. Potential factors for MDR includes enhanced drug detoxification, decreased drug uptake, increased intracellular nucleophiles levels, enhanced repair of drug induced DNA damage, overexpression of drug transporter such as P-glycoprotein(P-gp), multidrug resistance-associated proteins(MRP1, MRP2) and breast cancer resistance protein(BCRP). Currently nanoassemblies such as polymeric/solid lipid/inorganic/metal nanoparticles, quantum dots, dendrimers, liposomes, micelles has emerged as an innovative, effective and promising platforms for treatment of drug resistant cancer cells. Nanocarriers have potential to improve drug therapeutic index, ability for multifunctionality, divert ABC-transporter mediated drug efflux mechanism and selective targeting to tumor cells, cancer stem cells, tumor initiating cells or cancer microenvironment. Selective nanocarrier targeting to tumor overcomes dose-limiting side effects, lack of selectivity, tissue toxicity, limited drug access to tumor tissues, high drug doses and emergence of multiple drug resistance with conventional or combination chemotherapy. Current review highlights various nanodrug delivery systems to overcome mechanism of MDR by neutralizing, evading or exploiting the drug efflux pumps and those independent of drug efflux pump mechanism by silencing Bcl-2 and HIF1 gene expressions by siRNA and miRNA, modulating ceramide levels and targeting NF-B. “Theragnostics” combining a cytotoxic agent, targeting moiety, chemosensitizing agent and diagnostic imaging aid are highlighted as effective and innovative systems for tumor localization and overcoming MDR. Physical approaches such as combination of drug with thermal/ultrasound/photodynamic therapies to overcome MDR are focused. The review focuses on newer drug delivery systems developed to overcome MDR in cancer cell